2018
DOI: 10.1038/s41467-018-02865-1
|View full text |Cite
|
Sign up to set email alerts
|

Activated CD8+ T cell extracellular vesicles prevent tumour progression by targeting of lesional mesenchymal cells

Abstract: Fibroblastic tumour stroma comprising mesenchymal stem cells (MSCs) and cancer-associated fibroblasts (CAFs) promotes the invasive and metastatic properties of tumour cells. Here we show that activated CD8+ T cell-derived extracellular vesicles (EVs) interrupt fibroblastic stroma-mediated tumour progression. Activated CD8+ T cells from healthy mice transiently release cytotoxic EVs causing marked attenuation of tumour invasion and metastasis by apoptotic depletion of mesenchymal tumour stromal cells. Infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(142 citation statements)
references
References 45 publications
2
133
0
Order By: Relevance
“…Regulatory T cell‐derived EVs can work as suppressors against pathogenic Th1 responses in a miRNA‐dependent manner (Okoye et al, ). Seo et al found that EVs from activated CD8+ T cells were actively involved in interrupting tumor invasion and metastasis by depleting tumor mesenchymal cells (Seo et al, ). A similar performance was also observed for NK cells‐derived exosomes.…”
Section: Nanoparticle‐based Platforms For Cancer Immunotherapymentioning
confidence: 99%
“…Regulatory T cell‐derived EVs can work as suppressors against pathogenic Th1 responses in a miRNA‐dependent manner (Okoye et al, ). Seo et al found that EVs from activated CD8+ T cells were actively involved in interrupting tumor invasion and metastasis by depleting tumor mesenchymal cells (Seo et al, ). A similar performance was also observed for NK cells‐derived exosomes.…”
Section: Nanoparticle‐based Platforms For Cancer Immunotherapymentioning
confidence: 99%
“…A few years ago, significant differences had already been reported between the EVs released by tumour cells, which induce immunoregulation, compared to the EVs from immune cells, which induce immunomodulation [65]. A few examples have already been reported in this review [48,50,62]. Improvements developed recently are focused on the treatment of single or various cancers.…”
Section: Diagnosis and Therapymentioning
confidence: 81%
“…Surprisingly, CD8 + T cell exosomes exhibit cytotoxicity against tumor stromal cells such as MSCs and CAFs, but not tumor cells. In addition, CD8 + T cell exosome-mediated destruction of mesenchymal stroma associated with the reduction of tumor invasion and metastasis ( Figure 1) [13] .…”
Section: Exosomes From T Cells and Nk Cellsmentioning
confidence: 99%